Cultura de paz, um caminho de esperança para a educação - Hübner, Jussara Marques (2014)
This thesis has as its general goal to present the importance of the Culture of Peace examining the Sermon on the Mount in harmony with the Pillars of Bioethics and their contributions to the promotion of a Culture of Peace. And Education as an appropriate instrument in divulging and promoting a Culture of Peace with religion as a strong ally of science in the propagation of peace. The specific goals are: to present the World Movement of a Culture of Peace; contribute to the study of the Sermon on the Mount and the pillars of Bioethics in the promotion of the Culture of Peace; reflect on the role of the school as a propitious space for the implantation of a Culture of Peace without forgetting its challenges while maintaining hope and faith in better days; to present some of the challenges of the school today and possible ways out of the crises of contemporaneity within the schools. The thesis is divided into three chapters. The first deals with the Culture of Peace. The second is about the contribution of religion, specifically the Christian religion, through the Sermon on the Mount proffered by Jesus Christ, and the Pillars of Bioethics. And the last deals with the school as a propitious space for the implantation of a culture of peace. We dialogued with: Boff, Dreyfus, Nascimento, Engelmann, Milani, Dias, Noleto, Rodrigues, Sinner, Waiselfisz, Barchifotaine, Beauchamp, Brakemeier, Comte- Sponville Cescon and Nodari, Delors, Sales, Gadoti, Estáquio, Martin Lutero, Boock, D´Ambrósio, Lück, Aranha, Almeida, Chalita, Paulo Freire. The methodology used was bibliographic, researching in all the pertinent literature, ranging over various areas of knowledge, as well as in other means of information regarding the theme which covers all the bibliography already made public, from sporadic publications, bulletins, newspapers, journals, books, to other research, monographs, theses, etc. Where appropriate I used oral means of communication: radio, CDs and audio visuals: films and television. Therefore this research seeks to, in the first moment, theoretically substantiate, through bibliographic research and through the interlocution between religion and education, the possibility of behavioral change among school agents, from the head staff to the door keeper. Certainly, this peace which we desire is a reflection of the construction of values such as kindness, justice, equity, humility. The school space can become a propitious space for promoting a Culture of Peace as the goal of Educating for Peace.